THE THERMAL REGIMES OF THE UPPER MANTLE BENEATH PRECAMBRIAN AND PHANEROZOIC STRUCTURES UP TO THE THERMOBAROMETRY DATA OF MANTLE XENOLITHS - Glebovitsky V.A.; Nikitina L.P.; Khiltova V.Ya.; Ovchinnikov N.O. (My University, 2004)
The thermal state of the upper mantle beneath tectonic structures of various ages and types (Archaean cratons, Early Proterozoic accretionary and collisional orogens, and Phanerozoic structures) is characterized by geotherms and by thermal gradients (TG) derived from data on the P–T conditions of mineral equilibria in garnet and garnet–spinel peridotite xenoliths from kimberlites (East Siberia, Northeastern Europe, India, Central Africa, North America, and Canada) and alkali basalts (Southeastern Siberia, Mongolia, southeastern China, southeastern Australia, Central Africa, South America, and the Solomon and Hawaiian islands). The use of the same garnet–orthopyroxene thermobarometer (Theophrastus Contributions to Advanced Studies in Geology. 3: Capricious Earth: Models and Modelling of Geologic Processes and Objects 2000 44) for all xenoliths allowed us to avoid discrepancies in estimation of the P–T conditions, which may be a result of the mismatch between different thermometers and barometers, and to compare the thermal regimes in the mantle in various regions. Thus, it was established that (1) mantle geotherms and geothermal gradients, obtained from the estimation of P–T equilibrium conditions of deep xenoliths, correspond to the age of crust tectonic structures and respectively to the time of lithosphere stabilization; it can be suggested that the ancient structures of the upper mantle were preserved within continental roots; (2) thermal regimes under continental mantle between the Archaean cratons and Palaeoproterozoic belts are different today; (3) the continental mantle under Neoproterozoic and Phanerozoic belts is characterized by significantly higher values of geothermal gradient compared to the mantle under Early Precambrian structures; (4) lithosphere dynamics seems to change at the boundary between Early and Mezo-Neoproterozoic and Precambrian and Phanerozoic.
Keywords: Mantle; Xenoliths; Thermobarometry; Upper mantle; Geotherms; Thermal gradients; Thermal state; Precambrian; Precambrian; Докембрий